2018
DOI: 10.1093/mnras/sty1824
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic voids in evolving dark sector cosmologies: the high-redshift universe

Abstract: We compare the evolution of voids formed under the standard cosmological model and two alternative cosmological models. The two models are a quintessence model (φCDM) and a Coupled Dark Matter-Dark Energy (CDE) model, both of which have evolving and interacting dark sectors. From N-body adiabatic hydrodynamical simulations of these models, we measure the statistics and quantify the properties of voids over the redshift range z = 1.5 − 12: these include their population size, volumes, shapes and average densiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 79 publications
(101 reference statements)
0
19
0
Order By: Relevance
“…From Section 1 we stated the differences found between cosmologies by Adermann et al (2018) were that volumes of voids were found to be smaller yet emptier in the φCDM cosmology. This research was conducted using the same DM+Gas simulation suite we analyze throughout this paper.…”
Section: Movement and Migrationmentioning
confidence: 99%
“…From Section 1 we stated the differences found between cosmologies by Adermann et al (2018) were that volumes of voids were found to be smaller yet emptier in the φCDM cosmology. This research was conducted using the same DM+Gas simulation suite we analyze throughout this paper.…”
Section: Movement and Migrationmentioning
confidence: 99%
“…There has also been a significant effort to calculate the matter onepoint PDF from first principles [53,54] with the linear regime as a starting point, especially using a path-integral approach [55][56][57][58]. Finally, the study of cosmic voids has shed some light on the underdense tail of the one-point PDF [59][60][61][62][63][64], and simulation results can be turned into a reasonable PDF at low densities. We adopt b ¼ 1.5 following Ref.…”
Section: One-point Probability Density Functionsmentioning
confidence: 99%
“…Voids P voids ðδ b ; zÞ ϕ voids ðzÞg voids ð1 þ δ b ; zÞ Á Á Á ϕ voids is the fractional volume of the simulation in a void, g voids is the PDF of the mean 1 þ δ b in voids [64,66]. Only used for underdensities.…”
Section: One-point Probability Density Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…As revealed by these reviews and references therein: (i) cosmic voids enclose only 15% of cosmic matter-energy (within the ΛCDM paradigm) but cona e-mail: ismaeldg@icf.unam.mx b e-mail: hidalgo@icf.unam.mx c e-mail: sussman@nucleares.unam.mx stitute about 77% of cosmic volume; (ii) they form from early negative density contrast perturbations; (iii) they roughly keep their rounded shape and (iv) their dynamics is relatively insensitive to considerations from baryon physics. This relatively simple and pristine dynamics renders them as ideal structure systems to improve the theoretical modeling of generic cosmological observations [9][10][11], and to assess several open problems in cosmology: the nature of dark matter and dark energy [12][13][14][15][16][17][18][19][20][21], redshift space distortions [22][23][24][25], Cosmic Microwave Background (CMB) properties [26][27][28][29][30], Baryonic Acoustic Oscillations (BAO) [31], alternative gravity theories [32][33][34][35][36][37], local group kinematics and peculiar velocity fields [38][39][40][41][42][43][44], as well as theoretical issues such as gravitational entropy [45,46].…”
Section: Introductionmentioning
confidence: 99%